(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
This article is aimed to discuss the importance and benefits of learning languages. In addition, the important role of language in human life has been highlighted using scientific researches and sources of language. The article focuses on many areas of language learning, especially the importance of English, which is the main language of modern professions.